A qualitative evaluation of a mother and child center providing psychosocial support to newly arrived female refugees in a registration and reception center in Germany - Zehetmair, Catharina; Kindermann, David; Tegeler, Inga; Derreza-Greeven, Cassandra; Cranz, Anna; Friederich, Hans-Christoph; Nikendei, Christoph (International journal of environmental research and public health, 2021)
Female refugees are frequently exposed to sexualized, gender-based violence and harassment before, during, and after their flight. Yet female refugee-specific care and protection needs are rarely addressed in host countries. This study aimed to evaluate a mother and child center (MUKI) for female refugees in a reception and registration center in Germany. In 2017, we conducted semi-structured qualitative interviews with 16 female refugees attending the MUKI and with its five main staff members. We asked the participants about the MUKI’s relevance, encountered difficulties, and suggestions for improvement. The interviewees appreciated the MUKI’s sheltered environment, care services, and socializing opportunities, as well as its women-only concept. Overall, the participants saw overexertion, social engagement-related difficulties, and the MUKI’s noisy environment as key attendance barriers. Interviewed staff primarily reported problems regarding the working conditions, including the high staff and attendee turnover and low general service awareness. The participants advocated an expansion of the MUKI program. The MUKI project underlines that providing newly arrived, vulnerable female refugees with sheltered surroundings and psychosocial services is an essential step toward addressing female refugees’ specific care needs.
Gesehen am 02.07.2021
This article belongs to the Special Issue "Migration, Resilience, Vulnerability and Migrants’ Health"